Controllable Atomic‐Scale Sculpting and Deposition of Carbon Nanostructures on Graphene. Issue 9 (24th February 2014) - Xu, Tao; Xie, Xiao; Yin, Kuibo; Sun, Jun; He, Longbing; Sun, Litao
<x xml:space="preserve">Abstract</x> The physical processes and the relationships between focused electron beam‐induced sculpting and deposition based on graphene are investigated to realize controllable atomic‐scale nanofabrication on graphene. An improvement of the classical model is proposed to explain the experiments quantitatively. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>